Maimonides on the Fall of Man - Berman, Lawrence V. 1929-1988 (1980)
The forms of interpreting sacred texts are many, and, of course, the concept of sacred text is fluid and part of a process depending on the attitudes of society which change over time. For Maimonides, an important method of interpretation was the philosophical mode. In order to get a better understanding of what Maimonides understood by that method of interpretation, Chapter Two of the First Part of his Guide of the Perplexed on the fall of man is examined in terms of structure and content. Then, the principle underlying the possibility of the philosophic mode of interpretation of the Hebrew Bible according to Maimonides is discussed. Finally, the general place of the philosophic mode of interpretation within the general theory of the interpretation of literature is touched on briefly.